2012
DOI: 10.1589/jpts.24.715
|View full text |Cite
|
Sign up to set email alerts
|

Change of Muscular Activity and Dynamic Stability of the Knee Joint Due to Excessive and Repetitive Jumping or Cutting by Female Athletes

Abstract: Abstract.[Purpose] Previous studies have reported that physical activity is increasingly being encouraged as an essential part of a healthy lifestyle; thus, sports and preventable injury are becoming an important public health issue. Using an isokinetic test, we evaluated muscular activities and dynamic stability of the knee joint of skilled female athletes.[Methods] The subjects were 42 females aged 24.5 ± 0.9 years old, weighing 61.5 ± 1.1 kg; they were 169.6 ± 1.3 cm in height and had a body mass index (BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Skeletal muscle atrophy and joint contracture have proven to be significant orthopaedic problems in the area of physical therapy 3 , 17 , 18 ) . The skeletal muscle is the largest organ with high plasticity in the human, comprising about 50% of the total body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle atrophy and joint contracture have proven to be significant orthopaedic problems in the area of physical therapy 3 , 17 , 18 ) . The skeletal muscle is the largest organ with high plasticity in the human, comprising about 50% of the total body weight.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that cofilin in eukaryotic cells binds to actin and plays a role in actin dynamics and reorganization in cast immobilization- and starvation-induced atrophy in rat gastrocnemius muscles and L6 myoblasts 20 , 21 , 22 ) . However, further systematic and scientific studies in the fields of electrotherapy, neurotherapy, hydrotherapy and others are needed to confirm the mechanisms of PKB/Akt in atrophied muscle strips and cells 23 , 24 , 25 , 26 , 27 ) ( Fig. 1D ).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements were performed in October 2013. The participants also completed a questionnaire in an individual in-depth interview, which took 20 to 30 minutes per person 17 ) . The characteristics of the participants are shown in Table 1…”
Section: Methodsmentioning
confidence: 99%